2018
DOI: 10.1111/cas.13797
|View full text |Cite
|
Sign up to set email alerts
|

Comparative mutational evaluation of multiple lung cancers by multiplex oncogene mutation analysis

Abstract: In patients presenting with synchronous or metachronous multiple lung cancer (MLC), it is important to distinguish between multiple primary lung cancer (MP) and intrapulmonary metastasis (IM). The present study was aimed at investigating the mutational profiles of synchronous/metachronous MLC and to compare the classification of paired tumors by multiplex gene mutation analysis with the histopathological evaluation. We carried out targeted sequencing of 20 lung cancer‐related oncogenes using next‐generation se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 22 publications
4
30
0
Order By: Relevance
“…2 ) of the tumors from all patients were generated. EGFR alteration was the most frequently detected (77%), which was observed in 93.75% of patients (15/16), followed by TP53 alteration (32%), consistent with a previous study on multiple lung cancers reported in 2018 24 . Notably, RBM10 exhibited a significantly high mutation frequency (eight tumors, 25%) in stage I–II adenocarcinomas (32 tumors) (Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…2 ) of the tumors from all patients were generated. EGFR alteration was the most frequently detected (77%), which was observed in 93.75% of patients (15/16), followed by TP53 alteration (32%), consistent with a previous study on multiple lung cancers reported in 2018 24 . Notably, RBM10 exhibited a significantly high mutation frequency (eight tumors, 25%) in stage I–II adenocarcinomas (32 tumors) (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Considering that lung cancer usually displays a series of histological subtypes, different lesions often share overlapping histological features, which suggests that the morphology of MLC might not always be completely different. Therefore, the histological similarity between different tumors might be suggestive rather than conclusive 22 , 24 . In addition, lymph node metastases revealed that the two lesions were generated from the same clone.…”
Section: Discussionmentioning
confidence: 99%
“…This study sequencing only 20 genes had no equivocal cases, in part because some indefinite cases sharing only one hotspot driver mutation were classified as IM. 55 In other studies, 53,54,[56][57][58] relationship of 95% of lung adenocarcinomas although the most appropriate detection number of genes remains unknown. Additionally, as shown in Table 2, the molecular classification by NGS conflicts with the histological classification in many cases, and to some extent compensates for the shortcomings of a histological classification.…”
Section: Molecular Characteristicsmentioning
confidence: 99%
“…Subsequently, NGS screening from 20 to 468 cancer-related genes was applied to identify MPLCs. [52][53][54][55][56][57][58] Seven small studies enrolled a total of 237 patients (range, 11 to 60) and compared the diagnostic efficacy and robustness of the molecular classification with the different histological classifications (Table 2). Overall, NGS provides better discrimination than the clinicopathological classification because it is able to classify more indefinite cases, indicating the importance of NGS.…”
Section: Molecular Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation